Effect of High Cell Density to Lipid Content Microalgae Chlorella vulgaris on Photoautotrophic Cultivation: Effect of High Cell Density to Lipid Content Microalgae Chlorella vulgaris on Photoautotrophic Cultivation - Kevin Dyo Pamungkas; Khairul Anam; Titik Budiati (Food Science and Technology Journal (Foodscitech), 2023)
Chlorella vulgaris is one of microalgae types that has essential ingredients beneficial tohumans, such as being a source of good lipid. Chlorella sp. have high lipid content, up to30%, under autotrophic conditions considered as a promising candidate for commercial lipidproduction due to its fast growth and easy cultivation. High cell density sedimentation can beinvestigated as a starving method in cultivation to make microalgae conditions less favorablein obtaining nutrient to lipid accumulation. Starving is one of the stress conditions carried outwith the aim of reducing nutrients in the microalgae cultivation process. The aim of this studywas to determine the effect of high cell density on increasing lipid content in Chlorellavulgaris. The results of this study showed that high cell density method affected theproductivity of Chlorella vulgaris biomass. The data obtained were analyzed using ANOVAα=0.05. The highest productivity and lipid content was obtained from the control sample witha biomass value of 0.36±0.03 g/l and a lipid content of 56.2±4.6% (P<0.05). The conclusionof this study is high cell density may not increase the production of lipid content fromChlorella vulgaris